Human & technological resource management (HTRM) : new Insights into Revolution 4.0 - Kumar, Payal, 1966-; Agrawal, Anirudh; Budhwar, Pawan S. (Emerald Publishing Limited, 2020)
Industrial Revolution 4.0 is upon us, with disruptive technology rapidly changing our personal and professional lives. In this climate it is not clear how organization reorganization will take place and there is haziness over the strategic HRM required to attract, develop, and retain talent. This book shines a light on the rapidly changing work landscape by bringing together international expert contributors, who address issues such as the long-term effects of artificial intelligence and block chain technologies on the firm and on human resources, and deliberate on the effects Industrial Revolution 4.0 is likely to have on both emerging economies and developed countries. A number of fundamental questions are asked: Will HR managers perceive IT as a supporting adjunct or a core operational department? Will man and machine co-exist, or will artificial intelligence have more ominous implications for humanity, as predicted by Stephen Hawking? In other words, is HRM 4.0 an opportunity, a transient phase, or an impending threat? Human and Technological Resource Management is a must read for students and scholars of HRM, as well as anyone interested in the future of technology in the workplace, Review quote, 'The management of people in time of Industry 4.0 is a critical issue for both practitioners and academics. This book provides much needed answers from a cohort of leading academics who pull together current knowledge about HRM and Industry 4.0 to shed light on this complex matter. Those who study HRM would profit from reading this book', Prof Yehuda Baruch, Professor of Management, University of Southampton, UK.
Includes index.
Keywords: Personnel management -- Technological innovations.; Information technology -- Management.; Technological innovations -- Economic aspects.; Business & Economics -- Human Resources & Personnel Management.; Personnel & human resources management.; elektronické knihy; electronic books